2015
DOI: 10.1371/journal.pone.0134632
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-23 Receptor Gene Polymorphism May Enhance Expression of the IL-23 Receptor, IL-17, TNF-α and IL-6 in Behcet’s Disease

Abstract: PurposeRecent studies identified an association between Behcet’s disease (BD) and the IL-23R gene polymorphism (rs17375018) in different populations. This study examined whether this IL-23R gene polymorphism is associated with enhanced inflammatory responses.MethodsWe recruited 27 BD patients and 32 controls with three genotypes. Peripheral blood mononuclear cells (PBMCs) were seeded with or without anti-CD3 and CD28. Cells were incubated for 24 hours, and then supernatants were collected and stored at −20◦C u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…Samples were analyzed in duplicates, and mean cytokine levels were reported in pg/ml in each group. 15 The serum was analyzed to measure MPO, GPx, CT, NO, MDA, and SOD activity. The reagents used in this study were obtained from Sigma-Aldrich GmbH, Seelze-Germany, and Merck KGaA Darmstadt-Germany.…”
Section: Samplesmentioning
confidence: 99%
“…Samples were analyzed in duplicates, and mean cytokine levels were reported in pg/ml in each group. 15 The serum was analyzed to measure MPO, GPx, CT, NO, MDA, and SOD activity. The reagents used in this study were obtained from Sigma-Aldrich GmbH, Seelze-Germany, and Merck KGaA Darmstadt-Germany.…”
Section: Samplesmentioning
confidence: 99%
“…The IL-23R gene is mapped on chromosome 1p31, which reveals many SNPs listed in public SNP databases [33]. Lately, a lot of reports have shown that numerous single SNPs in the IL23R gene are correlated to immunerelated diseases, like inflammatory bowel disease, Crohn's disease, psoriasis, ankylosing spondylitis, and Behcet's disease [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the genetic variation of IL-17F and IL-23 A is associated with BD [36]. Jiang et al [37] reported that IL-23R gene polymorphism enhanced the expression of the IL-23 R and IL-17 in BD patients.…”
Section: Il-23-il-17 Axismentioning
confidence: 99%